1999
DOI: 10.1111/1467-8535.00121
|View full text |Cite
|
Sign up to set email alerts
|

The use of computer games as an educational tool: identification of appropriate game types and game elements

Abstract: During the past four years Alan Amory, a lecturer in Biology, has investigated the use of multimedia as a teaching resource and converted his courses from old-style lectures and practicals to constructivist-like classrooms. He also enjoys the thrill of creating software. Kevin Naicker, an Honours student at the time of this research, is interested in the use of computer technologies, especially the World Wide Web, in education. Jacky Vincent, our graphic artist, with her abounding enthusiasm and experience, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(159 citation statements)
references
References 14 publications
0
141
0
11
Order By: Relevance
“…For example, the inclusion of video games in teaching has been widely reviewed and scrutinized; and although the sophistication of the games does not permit content inclusion relevant to schooling yet, the development of parallel learning skills such as abstract thought, logic, memory, visualization and problem solving are valid elements worth encouraging through this media [23] Similarly," the affordances of Web 2.0 and social software" as exemplified by blogs, wikis, Facebook, etc… permit creative integration of information that gives rise to new and original thought unavailable prior to the development of these platforms [24].…”
Section: The Digital Dividementioning
confidence: 99%
“…For example, the inclusion of video games in teaching has been widely reviewed and scrutinized; and although the sophistication of the games does not permit content inclusion relevant to schooling yet, the development of parallel learning skills such as abstract thought, logic, memory, visualization and problem solving are valid elements worth encouraging through this media [23] Similarly," the affordances of Web 2.0 and social software" as exemplified by blogs, wikis, Facebook, etc… permit creative integration of information that gives rise to new and original thought unavailable prior to the development of these platforms [24].…”
Section: The Digital Dividementioning
confidence: 99%
“…There are different experiences of the use of competition (Verhoeff, 1987) and games (Amori, Naicker, Vincent, & Adams, 1999;Squire & Jenkins, 2003) in education. Although competition and games are different concepts, they have a relationship and most games introduce a certain degree of competition (against the computer or other opponents).…”
Section: Related Work and Innovation Of The Iscare Systemmentioning
confidence: 99%
“…In a study of learner preferences regarding elements of computer-based games, participant reactions to four commercial games -a strategy game, a simulation, a shooting game, and an adventure game -were gathered (Amory, Naicker, Vincent, & Adams, 1999). The researchers found that the simplest game was the most appealing (in this case, the shooting game) and the most complex game (in this case, the simulation) had the least appeal.…”
Section: Related Researchmentioning
confidence: 99%